Operation clean up: A model for eco-leadership and sustainability implementation. Issue 2 (March 2023) - Davies, Jessica F; Seglenieks, Richard; Cameron, Rose; Kuruvilla, Niketh A; Grove, Emma M; Shrivathsa, Archana; Grobler, Sophia
Healthcare contributes to environmental harm. Trainee-led Research and Audit in Anaesthesia for Sustainable Healthcare (TRA2 SH) is an Australasian network focused on sustainable anaesthesia practice. TRA2 SH hypothesised that trainee-led audits alongside education presented on a scheduled national day, called Operation Clean Up, can improve engagement with sustainability initiatives. This paper aims to describe the first two years of Operation Clean Up in terms of goals, achievements and data collected so far. Environmental themes for Operation Clean Up were chosen based on available evidence (life cycle analyses and observational studies). The first Operation Clean Up (OCU 2020) focused on reducing the unnecessary use of single-use disposable absorbent pads (known as 'blueys' in Australia, 'greenies' in New Zealand). OCU 2021 included: refuse desflurane, reduce bluey use, reuse drug trays, and recycle paper and cardboard. TRA2 SH provided an information pack to trainees who presented educational material to their department and fed back procurement figures to quantify each item. Descriptive statistics were used to analyse de-identified pooled data submitted to a centralised database. Eight departments submitted data for OCU 2020 and six provided follow-up data. Bluey use was reduced from a median of 37 to 34 blueys per ten surgical encounters. Fifteen departments submitted pre-campaign data for OCU 2021 with follow-up data to be collected during OCU 2022. Baseline data showed a median bluey use of 31 per ten surgical encounters. Volatile-related emissions were calculated; desflurane's proportion was 70% of these emissions yet was 11% of volatile procurement. Two participating departments removed desflurane from their formulary following OCU 2021. Operation Clean Up is a practical model for implementing sustainability initiatives using trainees as eco-leaders.